(untitled) (The Journal of Plant Protection Sciences, 2021)
Weeds cause heavy loss to the lentil (Lens Lentil variety B 256 (Ranjan) was sown at a row culinaris Medikus) crop as they rob the soil of spacing of 25 cm during December 04, 2003 its nutrients and moisture (1). The crop and November 30, 2004. The individual plot competes poorly with many weed species size was 4.0 m x 3.0m.